The Role of Place Attachment as a Mediator in the Effect of Destination Attractiveness on Environmentally Responsible Behavior in National Tourism Parks - Syafruddin Chan; Sorayanti Utami; Cut Aprilia (Proceedings of AICS - Social Sciences, 2020)
The purpose of this study is to test both direct and indirect hypotheses related to the determinants of environmentally responsible behavior and place attachment as a mediating variable in the ecotourism industry. Apart from local communities who must support eco-tourism activities in order to create sustainable ecotourism development, tourists must also give appreciation for environmental conservation activities in natural tourist destinations through various pro-environmental behaviors, collectively known as environmentally responsible behavior (ERB). 180 tourists visiting Gunung Leuser National Park (GLNP) in Sumatera, Indonesia were surveyed using convenience sampling technique. Structural Equation Modelling is used to determine the relationship between variables, encompassing analyses of direct and mediating effects. Of the three direct influence hypotheses, all of them are proven to have a significant effect. Meanwhile, the indirect effect of destination attractiveness on ERB through place attachments is proven to be insignificant. These findings suggest that the impact of place attachment to ERB is bigger than destination attractiveness, so ERB is better to be improved through place attachment than destination attractiveness.